Kink Effect Phenomenon in I-V Characteristic of Multiple-Gated AlGaAs/InGaAs HEMTs Device - Osman, M.N.; Awang, Z.; Rahim, A.I.A.; Yaakob, S.; Yahya, M.R.; Mat, A.F.A. (2007 Asia-Pacific Microwave Conference, 2007)
The electrical measurement to obtain output current characteristic of 0.2 mum AlGaAs / InGaAs HEMTs device has been performed within specific drain and gate bias voltages. The samples which consist a few layouts were designed based on different number of gate fingers to observe the effect towards the output characteristic performance. From the Ids-Vds characteristic, a sudden change in output current magnitude or kink effect is observed when the gate was biased at < 0.5 V. This kink effect condition was common for all layouts with different gate finger. However, the kink was so significant for device with higher gate finger. The phenomenon is due to the impact ionization in the GaAs buffer or substrate layer that allows electron trapped suddenly jump to the channel layer thus affecting the electron density magnitude in the channel. This sudden change in electron density in the channel cause the output current fluctuated and caused the kink phenomenon. The detail explanation of this phenomenon will be further discussed.